Set of 17 posters with title: Campagna elezioni politiche. 20 giugno 1976 (manifesti e inserzioni stampa) (1976)
Set of 17 posters with title: Campagna elezioni politiche. 20 giugno 1976 (manifesti e inserzioni stampa).